ANALISIS KESIAPAN SISWA FILIAL DAMBUNG RAYA DALAM MENGIKUTI ANALISIS NASIONAL BERBASIS KOMPUTER DI SMAN 1 BINTANG ARA KABUPATEN TABALONG - Syahrani; Radhia Shaleha; Auladina Shalihah (Bajang Institute, 2021)
The problem behind this research is the emergence of various perceptions regarding the readiness of filial students to receive education in the middle of the forest without electricity and internet connection in attending ANBK at SMAN 1 Bintang Ara, Tabalong Regency. The results showed that the readiness of Dambung Raya filial students in participating in the computer based national analysis at SMAN 1 Bintang Ara, Tabalong Regency belonged to the category of quite ready. This is supported by: the mental and physical readiness of the Dambung Raya filial students to take the computer based national exam at SMAN 1 Bintang Ara, Tabalong Regency, the unskilled students in operating computers, and the students mastery of the subject matter included in the ANBK, especially materials that have been completed discussed at school.